PENGARUH LINGKUNGAN KERJA, KUALITAS SUMBER DAYA MANUSIA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI - Mayang Krisnawida; Sundjoto; Sri Rahayu (Universitas Sarjanawiyata Tamansiswa, 2023)
This study examines the influence of the work environment, the quality of human resources and leadership style on employee performance at work. The sample in this study were 79 employees at the Bangkalan Tax Service Office. The analytical tool used is multiple linear regression. The results showed that simultaneously the work environment variables, the quality of human resources and leadership style have an effect on employee performance, while partially the work environment variables, the quality of human resources and leadership style have a significant effect on employee performance in the Bangkalan Tax Service Office.